2020
DOI: 10.3390/f11080814
|View full text |Cite
|
Sign up to set email alerts
|

Non-Financial Information Disclosures and Environmental Protection—Evidence from Romania and Greece

Abstract: Currently, sustainability and sustainable development are issues that concern society due to the high degree of pollution and the measures taken that, in many cases, do not prove their efficiency. Economic entities are aware that their involvement in the community has become necessary for the sustainable development of any business. The promotion of responsibility towards the environment is an important principle of corporate social responsibility (CSR), which is becoming an obligation that can no longer be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
2
25
0
1
Order By: Relevance
“…The trend analysis affirms hypothesis 1, which says mining companies comply with environmental information disclosure in China. The findings from our study are in line with the findings of Artene et al 2020 ; Giannarakis et al 2019 ; and Pan et al 2020 . Artene et al ( 2020 ) using a sample of 65 Romanian listed companies from 2011 to 2013 found that the environmental information disclosure trends have seen a major improvement over the past decade.…”
Section: Findings and Analysissupporting
confidence: 94%
See 2 more Smart Citations
“…The trend analysis affirms hypothesis 1, which says mining companies comply with environmental information disclosure in China. The findings from our study are in line with the findings of Artene et al 2020 ; Giannarakis et al 2019 ; and Pan et al 2020 . Artene et al ( 2020 ) using a sample of 65 Romanian listed companies from 2011 to 2013 found that the environmental information disclosure trends have seen a major improvement over the past decade.…”
Section: Findings and Analysissupporting
confidence: 94%
“…The findings from our study are in line with the findings of Artene et al 2020 ; Giannarakis et al 2019 ; and Pan et al 2020 . Artene et al ( 2020 ) using a sample of 65 Romanian listed companies from 2011 to 2013 found that the environmental information disclosure trends have seen a major improvement over the past decade. Similarly, Giannarakis et al ( 2019 ) show that companies which have established environmental management systems has made the greatest contribution to its environmental protection awards, and in effect have improved the trends of environmental disclosures.…”
Section: Findings and Analysissupporting
confidence: 94%
See 1 more Smart Citation
“…Some studies analysed the convergence of national laws transposing the NFI Directive (Aureli et al 2019;Aureli et al 2020). Other studies have verified how the new legislation contributes to the harmonisation of NFI reporting practices and how it can affect the level of disclosure (Dumitru et al 2017;Venturelli et al 2019;Mion and Loza Adaui 2019;Artene et al 2020). On an international level, Manes-Rossi et al (2018) analysed the compliance level of the 50 largest European companies, while Nicolò et al (2020) addressed the impact of the EU Directive on the NFI provided in the integrated reports of 22 European state-owned enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green growth is a model of the economy that improves human well-being and social justice while significantly reducing environmental risks and scarcity of environmental resources. The transition to a green economy depends on solving two related tasks to maintain the sustainability of ecosystems and identify ways to reduce the use of resources in production and consumption, as well as to reduce their impact on the environment (Artene et al, 2020).…”
Section: Introductionmentioning
confidence: 99%